If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + 5x + 5x = 68 Combine like terms: 5x + 5x = 10x -2 + 10x = 68 Solving -2 + 10x = 68 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 10x = 68 + 2 Combine like terms: -2 + 2 = 0 0 + 10x = 68 + 2 10x = 68 + 2 Combine like terms: 68 + 2 = 70 10x = 70 Divide each side by '10'. x = 7 Simplifying x = 7
| 5x-3=5x+3 | | 4.3-1.4*(p+7)=-9.7 | | 7x-8+6x=-8 | | x+3+2x=39 | | 9+7x=58 | | 3*-1.33333333333+4/7= | | -1.33333333333+4/7= | | p(x)=x^2-256 | | -7[3+7(-4+7)]+15= | | 3r+4= | | 3r+4/7=1 | | -2+3x=10 | | 7x+1=-48 | | 5(-4)-(-17)= | | 3x-x=74 | | 9n-17=46 | | 16s^2-9=0 | | -29+77= | | -19+-24+-16+-13= | | 6s^2-30s+24=0 | | 6-(-18)= | | 50+x+x=500 | | 5x^8y^6+25x^6y^5+10xy=0 | | 120+x+x=600 | | 9x+16=12x-8 | | -4x+10f=2 | | 2x=w(5y-11) | | 5+2x=23-x | | -154+11= | | -28+4= | | d-5=-25 | | (x-5)z=4y |